Leader and organization: the impetus for individuals' entrepreneurial orientation and project success - Ishfaq Ahmed; Ghulam Ali; Muhammad Ramzan (Journal of Global Entrepreneurship Research, 2014)
This study advances research on leader's & individuals' entrepreneurial orientation, organizational factors and project success in IT firms. This study adds value by taking entrepreneurial orientation of leader as leadership behavior rather than taking traditional leadership concepts, and investigates its outcomes in shape of individuals' entrepreneurial orientation. Using data collected from 42 teams of 25 IT firms, where sample consisting of 42 team leaders and 378 employees, we found that presence of organizational factors and leader's entrepreneurial orientation increases individuals' entrepreneurial orientation, which ultimately increases projects success. Overall, findings contribute by highlighting the significance of leader's and organizational role towards individual entrepreneurial role and performance. Findings are followed by recommendations and future directions.
Keywords: 650; Entrepreneurial orientation; Leader; Leadership; IT; Organizational factors